LgtF effects of Haemophilus parasuis LOS induced inflammation through regulation of NF-κB and MAPKs signaling pathways. (September 2017) - Zeng, Ze; Zhang, Bin; He, Huan; Chen, Xinnuo; Ren, Yupeng; Yue, Hua; Tang, Cheng
Abstract: The lgtF gene encodes a glucosyltransferase responsible for adding a glucose to the first sugar of heptose I in the synthesis of lipooligosaccharides (LOS). To study the function of lgtF, we constructed an lgtF mutant (Δ lgtF ) from Haemophilus parasuis SC096 using a natural transformation system. A highly purified preparation of LOS from Δ lgtF (Δ lgtF -LOS) exhibited an obvious truncation in structure compared to the LOS of the wild-type SC096 strain (WT-LOS). The Δ lgtF -LOS also displayed a significantly reduced ability to induce inflammatory cytokine mRNA expression of tumor necrosis factor alpha (TNF-α), interleukin-1α (IL-1α), IL-1β, IL-6 and IL-8 in porcine alveolar macrophages (PAMs) in comparison with the WT-LOS. Furthermore, we also found that Δ lgtF -LOS-treated cells had significantly decreased phospho-p65 and phospho-p38, and inhibited IκBα degradation. These findings suggested that the lgtF gene mediated LOS induction of pro-inflammatory cytokines in PAMs by regulating the NF-κB and MAPKs signaling pathways during H. parasuis infection. Highlights: The Δ lgtF from H. parasuis was constructed and its LOS exhibited an obvious truncation in structure. Δ lgtF -LOS displayed a significantly reduced ability to induce inflammatory cytokines expression. lgtF mediated LOS induction of inflammatory cytokines by regulation NF-κB and MAPKs pathways.